2020
DOI: 10.1080/1120009x.2020.1805239
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of leukoencephalopathy and its potential cognitive sequelae in cancer patients

Abstract: Due to the rising use of chemotherapy in cancer patients and growing survival rates, therapy-induced neurotoxic side effects are increasingly reported. Given the ambiguity about the prevalence and severity of leukoencephalopathy, one of such toxic side effects, in non-central nervous system (CNS) cancer patients, we performed a systematic literature search using the PubMed/Medline database to summarize existing literature regarding leukoencephalopathy epidemiology in non-CNS cancer patients and its potential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Secondly, the first MR examination for the children with ALL was scheduled for 1 to 3 days after complete remission was confirmed. The second MR examination was scheduled for at least 46 days after the completion of MTX treatment, by which point some asymptomatic children may have recovered from MTXrelated leukoencephalopathy and become negative on T1 WI and T2 WI (3,35). After intensive treatment, there might have impacted on the children's energy levels or psychological state, the effect of this on their cognitive scores cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the first MR examination for the children with ALL was scheduled for 1 to 3 days after complete remission was confirmed. The second MR examination was scheduled for at least 46 days after the completion of MTX treatment, by which point some asymptomatic children may have recovered from MTXrelated leukoencephalopathy and become negative on T1 WI and T2 WI (3,35). After intensive treatment, there might have impacted on the children's energy levels or psychological state, the effect of this on their cognitive scores cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotoxic side effects of MTX include leukoencephalopathy, which appears as transient, hyperintense regions on T2-weighted imaging (T2WI). In previous research, regularly scanning of patients with acute lymphoblastic leukemia (ALL) showed that leukoencephalopathy had a prevalence of between 17% and 87%, and 15% to 83% of patients presented with leukoencephalopathy when scanned only after a central nervous system event (3). Survivors of childhood ALL have been shown to experience treatment-related complications, such as secondary malignancies or neurocognitive impairment, which impact their quality of life after remission (4).…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have examined the prevalence of leukoencephalopathy in early-stage breast cancer patients. These studies either did not encounter treatment-associated leukoencephalopathy at all or only observed higher lesion load in patients showing neurologic symptoms [7,20]. This could partly be explained by different cancer types or stages and consequently other treatment regimens, as well as the heterogeneity in forms of observed lesions (for instance multifocal punctuate lesions are less easily detected).…”
Section: Introductionmentioning
confidence: 98%
“…MS], T2-weighted-Fluid-Attenuated Inversion Recovery (FLAIR) imaging is most often used, which shows white matter lesions (WMLs) as hyperintense regions [12]. High-dose chemotherapy is known to potentially cause MS-mimicking WMLs observable via FLAIR, or so-called leukoencephalopathy [20,21]. Additionally, post-mortem brain autopsies of former (metastatic) cancer patients treated with high-dose chemotherapy revealed demyelination in areas that showed WMLs on T2-weighted scans in vivo [22].…”
Section: Introductionmentioning
confidence: 99%
“…Functional neuroimaging approaches are incorporated as utilized in studies implementing multimodal neuroimaging approaches; however, a comprehensive review of functional neuroimaging studies in CRCD is beyond the scope of this review. Case studies [26][27][28] and reports on specific neurological effects such as leukoencephalopathy [29] are also not reviewed, and pediatric cancer populations are not discussed, given other recent reviews [e.g. , 30].…”
Section: Introductionmentioning
confidence: 99%